Reasoning with complex cases - Gebhardt, Friedrich, 1933- (Boston, Mass : Kluwer Academic, 1997)
Reasoning with Complex Cases emphasizes case retrieval methods based on structured cases as they are relevant for planning, configuration, and design and provides a systematic view of the case reuse phase, centering on complex situations. So far, books on case-based reasoning considered comparatively simple situations only. This book is a coherent work, not a selection of separate contributions, and consists largely of original research results using examples taken from industrial design, biology, medicine, jurisprudence and other areas. Reasoning with complex cases is suitable as a secondary text for graduate level courses on case-based reasoning and as a reference for practitioners applying conventional CBR systems or techniques.
Pt. I. Reasoning with Cases. 1. Introduction. 2. Reasoning with Complex Cases. 3. The Fabel Domain for Illustration -- Pt. II. Case Retrieval. 4. Case Similarities. 5. Similarities Between Attributes. 6. Restricted Geometric Relationships. 7. Graphs. 8. Semantic Nets. 9. Model-Based Similarities. 10. Enhancing the Quality of Retrieval Methods. 11. Conclusions and Perspectives -- Pt. III. Case Reuse. 12. Reusing Cases. 13. Reuse of a Single Case: Adaptation. 14. Reuse of Multiple Cases: Strategies. 15. Source Cases -- The Third Factor. 16. Conclusions and Perspectives -- Pt. IV. An Integrated System. 17. Designing Integrated CBR Systems. 18. Software Architecture. 19. Scenario of Application.
Includes bibliographical references (p. [227]-239) and index.
Also issued online.
Keywords: Case-based reasoning